Chronic insulin resistance deteriorates cardiac mitochondrial quality control in a mouse model of SEC-NAFLD-IR. (3rd October 2022) - Lu, K; Rothe, M; Floegel, U; Kotzka, J; Oehler, D; Roden, M; Kelm, M; Szendroedi, J; Westenfeld, R
Abstract: Background: Insulin resistance and nonalcoholic fatty liver disease (NAFLD) both relate to cardiovascular mortality. Using a mouse model of chronic lipid overload and secondary-NAFLD-induced insulin resistance (SEC-NAFLD-IR), we recently deciphered that SEC-NAFLD-IR already at young age provoked myocardial lipotoxicity with reduced mitochondrial efficiency and increased vulnerability to cardiac ischemia. However, long-term consequences of SEC-NAFLD-IR remain elusive. Purpose: Here we aimed to elucidate the impact of long-term SEC-NAFLD-IR on multiple mitochondrial quality control (mQC) mechanisms in the heart and its consequences for cardiac function. Methods: We studied 36 SEC-NAFLD-IR mice (72-week-old). For mechanistic experiments, we applied palmitate-induced insulin resistant murine HL-1 cells. Cardiac mitochondrial dynamics were measured via quantification of mitochondrial morphology and expression of mitochondrial fusion and fission factors (Opa1, Drp1, Fis1, Mfn 1 & 2). Mitophagy level was evaluated via immunofluorescence and protein expression of key mitophagy-related genes (Parkin, NIX, LC3). Mitochondrial biogenesis and mass were examined via quantitation of PGC-1α expression, mtDNA and citrate synthase activity. Results: 72-week-old SEC-NAFLD-IR mice exhibited 21% (p=0.001) and 32% (p<0.001) higher body weight and heart weight compared with controls. Along with elevated oxidative stress, hepatic lipid accumulation and inflammation, 6h-fasted SEC-NAFLD-IR mice were characterized by increased plasma glucose, insulin and cholesterol. SEC-NAFLD-IR mice displayed a cardiac phenotype with 21% higher left ventricular mass (normalized to body weight, p<0.001) and 6% lower ejection fraction compared to controls (73.5% SEM 0.90 vs 69.4% SEM 1.65, p=0.04). We found several advantageous mQC mechanisms suppressed in aged SEC-NAFLD-IR mice including long form OPA1-mediated mitochondrial fusion, Parkin- and NIX-mediated mitophagy. Likewise, mitochondrial biogenesis was suppressed in the aged insulin-resistant heart, which was connected to a 65% downregulation of PGC-1α1 expression (p=0.01). Interestingly, downregulation of cardiac PGC-1α1 in aged SEC-NAFLD-IR mice coincided with upregulation of PARIS, indicating the crucial participation of the Parkin/PARIS pathway in mQC of the insulin-resistant heart. In addition, induction of insulin resistance in murine HL-1 cardiomyocytes also led to increased mitochondrial fragmentation and decreased PGC-1α1 expression. Conclusion: This study demonstrated that regulation of mitochondrial network and turnover is hampered by SEC-NAFLD-IR in the hearts of aged mice, which may contribute to hypertrophy and cardiac dysfunction in insulin resistance. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Collaborative Research Centre 1116 (German Research Foundation)